Social Media and Body Dysmorphic Disorder (BDD): Is There Any Link? - khan, Wajiha; Yumna Zafar; Maryam Khalid (Journal of the Pakistan Medical Association, 2022)
To the Editor, Body Dysmorphic Disorder (BDD) is defined as a persistent and intrusive preoccupation with a non-existent or slight imperfection in one’s appearance. Being labelled as one of the obsessive-compulsive and related disorders, it has multifactorial etiology like cognitive deficits, psychological impairment and neurochemical abnormalities. However, a 2020 study has shed light on a more serious concern- it showed that the use of social media for longer duration, especially Snapchat and Instagram, are associated with increased incidence of BDD distinctly in young participants.1 Other researches have also highlighted this that social media can kindle the negative belief of body image by circulating photos, videos and comments about ideal self-image triggering insecurities especially in youngsters, about their physical features, body shape, complexion etc.2,3 Furthermore, social media platforms like Snapchat and Instagram are specialized in photo and video editing features, a behavior that is common in people with BDD.4 Fantasizing the celebrity ideals and social media influencers has promoted body dissatisfaction, disordered eating and other psychological comorbidities resulting in more frequent dermatological and psychiatric consultations.1 According to WHO approximately 24 million people in Pakistan need psychiatric assistance. Mental illness and psychological disorders still face persistent social taboo here. As only one psychiatrist is present for every 10,000 people in the country, BDD can become a big problem for the already feeble health system here by increasing the burden of mental illnesses. People here already consider white complexion the epitome of beauty and success, and promotion of similar mentality through social media either by celebrities or by influencers can be disastrous for the mental health of young individuals. That is why it is mandatory to dictate the proper and constructive use of social media. Facebook and Twitter trends can be set up for awareness and encouraging natural beauty instead of perfectly filtered dummy faces. As celebrities and influencers are followed by many, social media sites should promote people because of their intellect, talent and hard work rather than their appearances. These trivial steps can play a pivotal role in decreasing body dissatisfaction and concerns.